Synthesis of rhodamine-helicin fluorescent probe for colorimetric detection of Cu2+ and fluorescent recognition of Fe3+ - Jingxuan Sun; Yuxin Shao; Peng Li; Yang Yang; Chao-Ying Gao; Jinglin Liu (Sensors International)
Fluorescent probes play a crucial role in analytical chemistry and biological imaging, offering selective detection of metal ions. Herein, we present the synthesis and characterization of a novel rhodamine-based fluorescent probe, RbHC (Rhodamine B Helicin), which was obtained through the condensation of rhodamine B hydrazide and helicin in ethanol. The probe demonstrates remarkable selectivity and anti-interference capabilities towards Cu2+ and Fe3+ ions in 80% acetonitrile solution. Spectral titration analysis revealed a linear relationship between the intensity and the concentration of Cu2+/Fe3+. The formation of complex between Cu2+/Fe3+ and RbHC was confirmed to be 1:1, and it was further confirmed by ESI mass spectroscopy and DFT calculations. The coordination with Cu2+/Fe3+ caused the opening of RbHC's spirolactam ring, resulting in distinct color change and red fluorescence emissions. Moreover, RbHC exhibits high stability and water solubility under both acidic and neutral conditions, enabling its application in the imaging of plant tissues. Besides, the absorption intensity of RbHC–Cu2+ increased significantly when exposed to sunshine and 365 nm UV radiation, indicating that it might be used as a potential indicator for measuring outdoor UV intensity.